Utilization of gel electrophoreses for the quantitative estimation of digestive enzyme papain - Magdy M. Muharram; Maged S. Abdel-Kader (Elsevier, 2017)
SDS-PAGE densitometric method for analysis of papain in pharmaceutical formulations was developed and validated for the first time. Standard and samples were mixed with SDS sample buffer and denatured at 95 °C for 5 min and the gel was run at 20 mA and 200 V for 30-40 min in SDS-PAGE buffer. Gels were stained in Coomassie blue solution and distained by 5% methanol and 10% acetic acid. Destained gels were imaged and analyzed using the ChemiDoc™ XRS+ System. Bands of papain appeared at Rf value 0.78 ± 0.03 corresponding to molecular weight 23406 Da between proteins with molecular weight 31,000 and 21,500 Da of the broad range protein standard. The generated calibration curve was used for quantitative estimation of papain in pharmaceutical formulations. The developed method was validated for precision, accuracy, specificity and robustness as described by the ICH guidelines. The proposed method gives an alternative approach for enzymes and protein analysis.